A comparison of the effectiveness and success rate between prelocation of the nerves using percutaneous electrode guidance vs conventional technique for 3 in 1 block - Muhammad Nahar, Md Shahid (2008)
Peripheral nerve block provide analgesia and anaesthesia but the procedure itself can produce pain and discomfort to the patient This study evaluated the effectiveness of PEG for the prelocation of the nerves in the 3 in I block before nerve stimulator needle is introduced. The specific objectives of the study are to compare between PEG group and conventional group in terms of success rate, mean duration of performing 3 in I block, onset of blockade and number of attempts and redirection of nerve stimulator needle Prospective randomized single blinded study. Seventy orthopaedic patients with lower limb procedure were divided into 2 groups, group l (n=35) prelocation with PEG, group 2 (n=35) no prelocation/ conventional. Local anaesthetic agent used was 10ml 1% Lignocaine and 20ml 0.375% Ropivacaine There was no significant difference in success rate and mean duration of performing the 3 in 1 procedure, P value> 0.05. However the onset of sensory blockade was statistically significant, P value < 0.05, where group 1 patients (prelocate with PEG) showed faster onset than group 2 patients (without PEG). Group 1 also had statistically significant less number of redirection of nerve stimulator needle The use of PEG is effective in identifying the nerves with evidence of faster onset of blockade and reduces number of redirection of nerve stimulator needle but there was no statistically significant difference in success rate and duration of performing 3 in I block compared to conventional technique.